Campaña de comunicación para el Condominio Villa Panamericana - Arroyo Vidal, Fiorella Estefany (2019)
This paper develops a communication campaign for the sale of the departments of the Villa Panamericana located in Villa el Salvador, a condominium with modern infrastructure, eco-friendly, safe, with common areas at affordable price for the families of the socioeconomic level C and D of South Lima who care about their stability in the future. ATL, BTL, digital and public relations strategies were covered.